Global Brand Image: A Perspective of Turkish Consumers - Enginkaya, Ebru (INT MANAGEMENT DEVELOPMENT ASSOCIATION-IMDA, 2010)
Today increasing number of multinational companies have global marketing strategies for different countries. A challenge for many companies to become competitive is that they must build a consistent global brand image. Brand managers face many complex issues while managing their brands across diverse cultures and markets through out the world. This study will investigate consumer's thoughts, preferences, images associated with global brands. The aim of the research is about the determination of the brand image on consumer's purchase behavior for global coffee brand, Starbucks.
Keywords: PRODUCT; DIMENSIONS; LOYALTY; Business & Economics